Multi-facilities-based road network analysis for flood hazard management. Issue 1 (2nd January 2021) - Chakraborty, Omprakash; Ghosh, Soumya K.; Mitra, Pabitra
ABSTRACT: Disaster management requires the coordinated provision of multiple service facilities. Road networks play an important role in facilitating access paths to such services from settlements, particularly during flood disasters. The importance of a road depends on its utility along with its geospatial characteristics. In this article, we propose road importance measures that consider spatial properties, the serving utility and nature of interaction of the services. A multilayer graph-based approach is proposed for this purpose. The methodology includes different proposed metrics that are utilized to grade and identify optimal links of network access paths even in severe conditions. A case study is presented for a flood scenario with the associated services being relief shelters, relief storage centres and hospitals. It has been shown that the multi-layered approach provides a more realistic assessment of the road importance as compared to conventional link analysis. The identification of optimal road links helps in several mitigation and rescue strategies for disaster management.